Precise modeling of a four wheeled omni-directional robot - Hélder Filipe Pinto de Oliveira (2008)
Recent applications in Autonomous Robotics are becoming more demanding every day. Modern Mobile Robots use Omni-Directional locomotion in order to achieve additional maneuverability and efficiency. These features are gained at the expense of increased mechanical complexity and increased complexity in control. Demanding applications require precise dynamical model in order to allow for precise locomotion. Dynamical Models are also essential to study limitations of current mechanical configurations and to allow for future enhancements both at controllers level and at mechanical configuration level. The presented work finds a precise dynamical model for a 4 wheeled omni-directional robot and a prototype is used for validation. Simulations and real experimental runs are shown and the adequacy of the model is discussed.